URGENSI APLIKASI DIGITAL DAN LEGAL DRAFTING PERATURAN DESA BERDASARKAN PERDA NO. 5 TAHUN 2016 BAGI BADAN PERMUSYAWARATAN DESA - Mulyanto Mulyanto (Journal of Law, Society, and Islamic Civilization, 2016)
The purpose of writing to know Bekonang BPD and BPD Plumbon able to use Digital village regulation Application Program. In addition, in order to formulate appropriate legal language Perdes concept of legal drafting. Methods used include training, practice and mentoring. The results showed that, First, the digitization process village regulation using OpenOffice software application into Perdes digital archive management. Records management application is a web-based application built using opensource and legal tools to be used without a license. So that the resulting application is an application that is legal. Secondly, in the process of preparation of Perdes as stipulated in Bylaw No. 5 of 2016 which started from (a) Planning; (b) Preparation of the Village Head and BPD; (c) Discussion; (d) Determination; (e) promulgation; (f) Dissemination; and (g) Evaluation and Clarification of Village Regulations. Based on the questionnaire village regulation concluded the drafting legal training gives benefit to BPD Bekonang and Plumbon, Sukoharjo.Keywords: legal drafting, Digital Perdes, village regulation